Classroom Interaction In English Speaking Class (A Study at SMA Santu Fransiskus Ruteng, Flores) - Gabriel Fredi Daar (Yayasan Visi Intan Permata, 2020)
Classroom interaction emphasizes on the effectiveness of the students participation in the dialogue, and finally improving the ability of speaking. It involves all participants; teacher, learners and learning sources. There are some different purpose of using speaking. Each purpose implies knowledge of the rules that account for how spoken language reflects the context in which the speech occurs (Richard and Renandya, 2002:201). The study aims at finding out how classroom interaction employed in speaking class at SMA Santu Fransiskus Ruteng, Flores. It’s used mixed method combining the use of descriptive quantitative and qualitative study design with phenomenological approach. It’s used random sampling, with 45 students taken as the samples. Meanwhile, employing a qualitative research design and phenomenological approach, the data for this study are mostly collected through interview completed by observation and documentation. For the purpose of deep interview, the participants are 1 English teacher and 4 students taken purposively. The study showed that 1) there is one aspect of classroom interaction mostly categorized as high level of implementation; Response and Asks Questions (28=62.2%). Data of interviewed confirmed that students needs appreciation for learning progress or achievement they may make. It encourages them to be more active and participative. 2) Feelings acceptance, praises or encouragement, and ideas use or acceptance implementation (40=88.9%) and giving directions, criticisms or authority justification (38=84.4%) were mostly in the category of medium level. Meanwhile, initiation was mostly in the category of low level (24=53.3%). Data of interview confirmed that low initiation is caused by students learning habit. Most students do the activities of learning English when English teacher fosters them to learn. It’s in the form of quiz, assignment, mid test or final test. Leaning is merely conducted to improve and increase English score. Other activities such as memorizing vocabularies, writing stories, answering questions based on the passages, building up sentences and other classroom activities designed are done under teacher’s control and design. In the next phase, students find it difficult to accomplish complex tasks. They are only able to accomplish simple tasks. Learning autonomy which is oriented to build up speaking ability hardly ever done. To this extend, English teacher pay more attention to the topic chosen in teaching learning processes. It determines whether the students initiate interaction or not.